Sex Differences in Mate Preferences Across 45 Countries: A Large-Scale Replication - Walter, Kathryn V.; Conroy-Beam, Daniel; Buss, David M.; Asao, Kelly; Sorokowska, Agnieszka; Sorokowski, Piotr; Aavik, Toivo; Akello, Grace; Alhabahba, Mohammad Madallh; Alm, Charlotte; Amjad, Naumana; Anjum, Afifa; et al. (SAGE Publications, 2020)
Considerable research has examined human mate preferences across cultures, finding universal sex differences in preferences for attractiveness and resources as well as sources of systematic cultural variation. Two competing perspectives—an evolutionary psychological perspective and a biosocial role perspective—offer alternative explanations for these findings. However, the original data on which each perspective relies are decades old, and the literature is fraught with conflicting methods, analyses, results, and conclusions. Using a new 45-country sample (N = 14,399), we attempted to replicate classic studies and test both the evolutionary and biosocial role perspectives. Support for universal sex differences in preferences remains robust: Men, more than women, prefer attractive, young mates, and women, more than men, prefer older mates with financial prospects. Cross-culturally, both sexes have mates closer to their own ages as gender equality increases. Beyond age of partner, neither pathogen prevalence nor gender equality robustly predicted sex differences or preferences across countries. © The Author(s) 2020.